Kreativitas Guru Dalam Membuat Alat Permainan Edukatif Dari Barang Bekas - Mukti Wigati; Novan Ardy Wiyani (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2020)
The main problem that is the focus of this research is the process of making educational toys with used goods in TK IT Al Fattaah Sumampir Purwokerto. This study aims to describe TK IT Al-Fattaah Sumampir Purwokerto in the manufacture of educa- tional game tools with used goods. This research is a descriptive qualitative research. The method in collecting data that I use is observation, interview and documentation. Where- as in data analysis using the method of reducing data, presenting data, and inferring data. The results of this study indicate that TK IT Al-Fattaah Sumampir Purwokerto has tried to make their own educational game tools with used goods. In making educational game tools there are three stages, namely the determination of tools and materials, the manu- facturing process, the use of educational games tools with used goods, and evaluation process to educational games.